Massive pulmonary embolism: embolectomy or extracorporeal membrane oxygenation?. Issue 6 (December 2019) - Tahir, Usman A.; Carroll, Brett; Pinto, Duane S.
Abstract : Purpose of review: To highlight updates on the use of extracorporeal membrane oxygenation (ECMO) and surgical embolectomy in the treatment of massive pulmonary embolism. Recent findings: Outcomes for surgical embolectomy for massive pulmonary embolism have improved in the recent past. More contemporary therapeutic options include catheter embolectomy, which although offer less invasive means of treating this condition, need further study. The use of ECMO as either a bridge or mainstay of treatment in patients with contraindications to fibrinolysis and surgical embolectomy, or have failed initial fibrinolysis, has increased, with data suggesting improved outcomes with earlier implementation in selected patients. Summary: Although surgical embolectomy continues to be the initial treatment of choice in massive pulmonary embolism with contraindications or failed fibrinolysis, the use of ECMO in these high-risk patients provides an important tool in managing this often fatal condition.